INFRARED DRYING KINETICS OF BLUE MUSSELS AND PHYSICAL PROPERTIES - Kipcak, Azmi Seyhun; Doymaz, Ibrahim; Derun, Emek Moroydor (ASSOC CHEMICAL ENG, 2019)
As an alternative to fish and beef, blue mussles (Mytilus edulis) can be consumed due to their high protein content. In this study, the drying kinetics and quality changes (cook loss, area shrinkage and colour change) in whole blue mussels were investigated with several infrared power levels between 88-146 W. Various thin-layer drying models were applied to the blue mussel and the Midilli et al., model best fits the experimental data (R-2: 0.999150-0.999750,chi(2): 0.000104-0.000030, RMSE: 0.008309-0.004797). The effective moisture diffu-sivity was determined to be between 4.24x10(-9) and 1.10x10(-8) m(2)/s. The activ-ation energy was found to be 20.85 kW/kg. The cook loss and area shrinkage increased with increasing power level and drying time. Most cook loss (30%) and area shrinkage (30%) were obtained between 15-23 min and 8-20 min of drying time, respectively. The colour change was slightly affected by the change in infrared power level.
Keywords: activation energy; blue mussel; effective moisture diffusivity; infrared drying; colour change; QUALITY CHANGES; MICROWAVE; SLICES; MUSCLE; Chemistry; Engineering